Behaviours of shooter and goalkeeper interact to determine the outcome of soccer penalties - Hunter, A. H.; Angilletta Jr., M. J.; Wilson, R. S. (Scandinavian Journal of Medicine & Science in Sports, 2018)
During a soccer penalty, the shooter's strategy and the goalkeeper's strategy interact to determine the outcome. However, most models of penalty success overlook its interactive nature. Here, we quantified aspects of shooter and goalkeeper strategies that interact to influence the outcome of soccer penalties - namely, how the speed of the shot affects the goalkeeper's leave-time or shot-blocking success, and the effectiveness of deceptive strategies. We competed 7 goalkeepers and 17 shooters in a series of penalty shootout competitions with a total of 1278 shot taken. Each player was free to use any strategy within the rules of a penalty shot and game-like pressure was created via monetary incentive for goal-scoring (or blocking). We found that faster shots lead to earlier leave-times and were less likely blocked by goalkeepers, and—unlike most previous studies—that deceptive shooting strategies did not decrease the likelihood goalkeepers moved in the correct direction. To help identify optimal strategies for shooter's and goalkeepers, we generated distributions and mathematical functions sport scientist can use to develop more comprehensive models of penalty success.